Hallux valgus interphalangeus: reliability of radiological assessment. Issue 4 (August 2019) - Hujazi, Ihab; Yassa, Rafik; Sevenoaks, Hannah; Khalfaoui, Mahdi; Barrie, Jim
Highlights: Reliable radiographic measurement of hallux valgus interphalangeus deformity has a role in guiding surgical management. Three observers assessed the radiological measurements and intra-class correlation coefficients were calculated to assess agreement. Reliability is good to excellent among the radiological techniques used to assess hallux valgus interphalangeus. Abstract: Background: Reliable radiographic measurement of hallux valgus interphalangeus (HVI) deformity has a role in guiding surgical management. HVI can be assessed using: Hallux interphalangeal angle (HIA). Distal articular set angle (DASA). Proximal to distal phalangeal articular angle (PDPA). The aim of the study is to investigate the reliability of these radiological parameters. Methods: Seventy foot radiographs in patients pre and post hallux valgus corrective surgery were assessed by 3 observers. HVI was assessed using the radiological measurements described above. Two-way random, single measure intra-class correlation coefficients were calculated to assess agreement. Results: Inter-observer reliability showed good agreement for DASA [ICC = 0.77(0.61–0.88)], and excellent for HIA [ICC = 0.92(0.85–0.96)] and PDPA [ICC = 0.91(0.84–0.96)]. Intra-observer reliability was excellent for all angles; DASA [ICC = 0.88 (0.76–0.95)], HIA [ICC = 0.94(0.86–0.97)] and PDPA [ICC = 0.83(0.65–0.92)]. Conclusions: Reliability is good to excellent among these three radiological techniques for assessing HVI. The HIA and PDPA are slightly more reliable.